Relevansi Model Pembelajaran Radec sebagai Strategi Pembelajaran IPS - Bahri, Bahri; Akbar, Muh.; Tati, Andi Dewi Riang (Universitas Negeri Makassar, 2025)
Learning in the 21st century requires educators to be able and capable of carrying out learning processes aimed at developing students' skills according to the needs of the 21st century. Skill formation can be realized in one way, namely social studies educators acting as learner centers or learning that makes students the subject of learning. In addition, social studies learning strategies through the selection of appropriate learning models also play an important role in supporting the achievement of student skill formation according to the needs of the 21st century. One of the learning models designed according to the conditions of education in Indonesia in the 21st century is the Radec learning model. This study aims to determine the relevance of the Radec learning model as a social studies learning strategy in junior high schools in the 21st century. By using qualitative methods, the author constructs a discussion of research problems, data analysis techniques using literature reviews in the form of books and reviews of relevant research articles. Based on the review of books and journals, the results of this study conclude that there is relevance of the Radec learning model as a social studies learning strategy in junior high schools in the 21st century. The Radec learning model can build students' critical thinking skills in social studies learning.